The Problem of Beauty as a Prism of Good and its Pedagogical Implications - Sylwia Jaronowska (Maria Curie-Skłodowska University, Lublin, Poland, 2023)
Introduction: The research issues undertaken in this article concern beauty from perspective of the role in which it becomes a prism of good. The presented theoretical analyzes of the discussed concepts and phenomena reference was made to the need to use beauty as a prism of good in education and upbringing, indicating that the fulfillment of this need is an important reponse to contemporary educational challenges. Research Aim: The aim of the undertaken analysis is to draw attention to the possibilities of using this aspect of the impact of beauty in education, wherein experiencing it becomes an experience sensitizing to good, triggering a longing for good and beauty, and inspiring to search for these values in one's own life. Evidence-based Facts: The presented analyses, based on references to source literature, refer to the ancient interpretation of beauty as a category with ethical, spiritual and aestetic dimensions. References were made to the views in which attention is paid to contemporary cultural tendencies that are an expression of references to beauty, references far from its understanding as a value combined with good. Reference was also made to the views of these representatives of pedagogical thought who attention to the neglect of the value of beauty in modern upbringing. Summary: The presented analyzes are concluded with the conclusion that the educational dimensions of the impact of beauty as a prism of good should be associated with shaping sensitivity to beauty and awakening the need to implement this value in activities that are an expression of affirmation of the inseparable triad - truth, good and beauty.